101k views
3 votes
How do I solve this?

How do I solve this?-example-1
User ViToni
by
5.5k points

1 Answer

3 votes

Answer: A

One solution x = 60/23 y=12/23 z= -72/23

How? in the photos attached

Explanation:

Take the first equation and rewrite

5x +y = 1 becomes y = 1 -5x

Substitute for y in the second equation

Solve for x

The rest of the steps are more of the same: substitute and solve as scownin the photos

They overlap a bit to be sure it's all there

How do I solve this?-example-1
How do I solve this?-example-2
User Wisequark
by
5.3k points